Google Groups no longer supports new Usenet posts or subscriptions. Historical content remains viewable.

Dismiss

16 views

Skip to first unread message

Jan 8, 2005, 11:06:52 AM1/8/05

to

Is it possible to solve equation y(f(x))=y(x)+x if f(.) is a known

function? (e.g., f(x)=exp(x)-1 ?)

function? (e.g., f(x)=exp(x)-1 ?)

Jan 9, 2005, 8:56:27 AM1/9/05

to

Maxim wrote:

>Is it possible to solve equation y(f(x))=y(x)+x if f(.) is a known

>function? (e.g., f(x)=exp(x)-1 ?)

>

>

If f(0)=0 and f is differentiable at 0 with f'(0)=1, as in the case

f(x)=exp(x)-1, then there is no solution y which is differentiable at 0.

PROOF: Assume that y is differentiable at 0. Then so is y°f. For x not

equal to 0, we have [(y°f)(x)-(y°f)(0)]/x - [y(x)-y(0)]/x = 1; so for x

-> 0, we obtain 1+y'(0) = (y°f)'(0) = y'(f(0)) f'(0) = y'(0), a

contradiction.

-- Marc Nardmann

Jan 9, 2005, 3:24:47 AM1/9/05

to

In article <vz6xjmdri49p@legacy>, Maxim <MOsa...@nes.ru> wrote:

>Is it possible to solve equation y(f(x))=y(x)+x if f(.) is a known

>function? (e.g., f(x)=exp(x)-1 ?)

>Is it possible to solve equation y(f(x))=y(x)+x if f(.) is a known

>function? (e.g., f(x)=exp(x)-1 ?)

What do you mean by "solve"?

Exactly this example is treated as a prototype for a broad family of

similar problems in a paper by Szekeres; he argues that there is one

particularly optimal solution y and in an accompanying paper provides

tables of numerical values. (He uses the analysis to describe a

one-parameter family of functions f_s with f_s o f_t = f_{s+t} and

in particular describes a functional "square root" f_{1/2} of f = f_1.)

MR0141905 (25 #5302)

Szekeres, G.

Fractional iteration of exponentially growing functions.

J. Austral. Math. Soc. 2 1961/1962 301--320. MSC section 39.99

dave

Jan 11, 2005, 2:33:02 AM1/11/05

to

http://www.research.att.com/cgi-bin/access.cgi/as/njas/sequences/eisA.cgi?Anum=A052122

for f(x) such that f(f(x)) = exp(x)-1.

Daniel

Jan 13, 2005, 1:33:41 PM1/13/05

to

Dear All,

We may show that if it exists m |f(x)= m^[x](x) xth iterate of m(x)

equation y(f(x))=y(x)+x is equivalent to y(m(x)= y(x) + 1 (sci.math 09

june ).

So with f(x)=exp(x)-1 you have to find m^[x](x)= exp(x)-1 ,an harder

task than solving or computing m(x) from m(m(x))= exp(x)-1 ,

Sincerely,Alain.

Jan 16, 2005, 8:15:00 PM1/16/05

to

Dear friends,

Very often we may build y(x)as a function point to point .

Here y(f(x))=y(x)+x then from y(x0) , y(f(x0))=y(x0)+x0 ....

in fact we've got:y(f^[n](x0)=y(f^[n-1](x0))+f^[n-1](x0) or

y(f^[n](x0)=y(x0)+x0 +f(x0)+f^[2](x0)+....

f^[n](x0) stands for f(f(f(f(f(f (x0)..))) f n times.

In our case we must choose x0 # 0 (to avoid y(0)=y(0)+0 a loop!).

two consequences:

value y(x0) is 'free',

we obtain a'gruyère',that is to say a holy swiss cheese:function is

known only in points x0, f(x0),....f^[n](x0).

Sincerely,Alain.

0 new messages

Search

Clear search

Close search

Google apps

Main menu